SLOPE STABILITY ANALYSIS OF UNSATURATED CLAY SOIL UNDER FREEZE-THAW AND RAINFALL INFILTRATION EFFECTS - Amantay, Aiym (Nazarbayev University School of Engineering and Digital Sciences, 2024)
This thesis examines how rainfall infiltration and freeze-thaw cycles affect the slope stability of unsaturated clay soils in Kazakhstan. The effect of these environmental factors makes slope vulnerable to landslides by changing soil’s thermal and hydraulic properties. To analyze the impact of rainfall infiltration and freeze-thaw cycles, this study uses GeoStudio software in order to understand how environmental stresses affect slope stability. Three different modules were used to assess Factor of Safety: TEMP/W, SEEP/W, and SLOPE/W. Moreover, 5 various cases of simulations were highlighted and added to study: change in soil properties, temperature variations, soil types, evaporation rate, etc. The numerical simulation was done using results of laboratory works for soil properties such as SWCC curve and unsaturated permeability values along with rainfall and temperature data for Almaty climate. The results suggest that the main impact is from rainfall infiltration as it significantly lowers the Factor of Safety of Soil. Using SEEP/W results, paper found that even incorporation of evaporation effect was less effective in recovery of Factor of Safety of Soil as the main influence was still from rainfall. This paper further analyzed TEMP/W results by adding temperature fluctuations, however influence was not very large.
Keywords: type of access: embargo; slope stability; rainfall effect; freeze-thaw cycle effect; numerical simulation